Connecting the dots: the case of foreshadow and meaning in pantun / Nazima Versay Kudus and Melati Desa - Versay Kudus, Nazima; Desa, Melati (Academy of Language Studies, 2022)
Pantun was primarily expressed in oral form. With the advent of printing presses in the late 19th century, compilations of pantuns in numerous dialects of the language have been published. Its creative verse format has captured the imagination of people and scholars within and outside the local region where it has originated. It is regarded indigenous and distinctive, and a microcosm of Malay life, ideas, and aesthetics. According to Muhammad (2006), the Malay intellect, wisdom, and beautiful shades of meaning and expression are found in pantuns more than anywhere else. The Malay pantun consists of two parts: the pembayang (prefatory statement) and the maksud or isi (meaning or message). In good pantuns, both parts are not arbitrary; they are connected and intertwined based on Oriental philosophy in general and Malay philosophy in particular (Tran, 2013).